REACTION OF THYMUS TU DPT VACCINATION IN CHILDREN AS ASSESSED BY ULTRASONOGRAPHIC STUDIES - O. B. Sirotina (Медицинская иммунология)
When performing ultrasonography of thymus in young children, we have revealed a specific phenomenon, i.e., a significant increase of thymus size in the children of 4 to 6 months old, having been observed at the terms of vaccination with a combined dyphteria/pertussis/tetanus (DPT) vaccine. After examining the dimensions, volume, mass and features of thymic blood flow, we have found that, during the DTP vaccinations, 88.7% of the children exhibit an increase in thymic dimensions, along with higher blood flow rates, as compared with the same indices in unvaccinated children. In 11.3% per cent of the cases, the vascularization of thymus was not altered at all, or did not show any changes. To our mind, these ultrasonic parameters of thymic status represent a regular reaction of a key immune organ to a challenge with bacterial antigens, i.e., being an indicator of the primary immune response to DTP vaccination.